2005
DOI: 10.1080/13547500500094034
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomics with1H-NMR spectroscopy and liquid chromatography-mass spectrometry applied to the investigation of metabolic changes caused by gentamicin-induced nephrotoxicity in the rat

Abstract: The model nephrotoxin gentamicin was administered to male Wistar-derived rats daily, for 7 days, at 60 mg kg-1 day-1, subcutaneously, twice daily. Conventional clinical chemistry urinalysis showed a significant increase in N-acetyl-beta-D-glucosaminidase (NAG) activity from day 3. At necropsy on day 9, clear histological damage to the kidney was noted with all animals showing a generally severe nephropathy primarily focused on the proximal convoluted tubules. The urinary excretion pattern of endogenous metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 15 publications
3
91
0
3
Order By: Relevance
“…36 Depletion of hippurate and PAG has been reported after ingestion of antibiotics such as vancomycin 12 and gentamicin. 37 In addition, gastrointestinal microbial analysis of fecal samples from children with late-onset autism has shown that autistic individuals have higher incidence of the Clostridium histolyticum group of bacteria, as well as increased diversity of clostridial species 11,13 , and individuals with autism have been shown to have abnormalities in hippurate excretion. 38 Abnormalities of the gut microbiota including the Clostridium sp.…”
Section: Discussionmentioning
confidence: 99%
“…36 Depletion of hippurate and PAG has been reported after ingestion of antibiotics such as vancomycin 12 and gentamicin. 37 In addition, gastrointestinal microbial analysis of fecal samples from children with late-onset autism has shown that autistic individuals have higher incidence of the Clostridium histolyticum group of bacteria, as well as increased diversity of clostridial species 11,13 , and individuals with autism have been shown to have abnormalities in hippurate excretion. 38 Abnormalities of the gut microbiota including the Clostridium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm previous studies where quantitative changes by NMR spectroscopic metabolite patterns provided information on the location and severity of toxic lesions. Those studies detected the presence of glucosuria and aminoaciduria after exposure to known proximal tubule nephrotoxins such as gentamicin, mercuric chloride, and D-serine (7,8,48). Glucosuria and enhanced excretion of amino acids are both strong indicators of proximal tubule damage in general, likely caused by impaired tubular reabsorption in the proximal tubule via sodium-dependent glucose transport.…”
Section: Effect Of Cisplatin and Fibrate (Wy) On Serum Levels Of Insulinmentioning
confidence: 99%
“…A further application was investigated by Dieterle et al (2006), who reported a metabolomics analysis in a compound ranking study, which revealed increased excretion of choline in rat urine. Several other reports have been published on the metabolomic analysis of individual nephrotoxins, such as cadmium chloride (Griffin et al 2001), mercury chloride (Holmes et al 2000), gentamicin (Lenz et al 2005), cisplatin (Portilla et al 2006), and aristolochate (Ni et al 2007), among others. Finally, a large comprehensive study was reported from the Consortium on Metabonomic Toxicology (COMET) (Ebbels et al 2007), in which many nephrotoxins were analyzed, to build prediction and classification models for drug toxicity.…”
Section: Introductionmentioning
confidence: 99%